An Overview of Impulse Purchase Behavior on F-Commerce Platform in Sumatera, Indonesia - Rahayu, Fadilla Riska; Hayu, Rina Suthia; Hadi, Effed Darta (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 16 Nomor 1 Tahun 2022, 2022)
This study aims to examine the effect of f-commerce browsing and f-commerce usage intensity of f-commerce impulse purchase mediated by urge to purchase on users of the Facebook. The data was collected from 197 respondents who had made impulsive purchases using the Facebook. The data collection technique used a questionnaire that was distributed online through social media. The research measurement in this questionnaire consists of 16 questions to the respondent. Data analysis in this study used SEM-AMOS to see the relationship between variables. the research showed that; (1) f-commerce browsing has a positive effect on f-commerce impulse purchase; (2) f-commerce usage intensity has a positive    effect on f-commerce impulse purchase; (3) f-commerce browsing has a positive effect on urge to purchase; (4) f-commerce usage intensity has a positive effect on f-commerce urge to purchase; (5) urge to purchase has a positive effect on f-commerce impulse purchase; (6) urge to purchase mediates the effect of f-commerce browsing on f-commerce impulse purchase; (7) urge to purchase mediates the f-commerce usage intensity on f-commerce impulse purchases.